Parents Role In Optimizing Independence Children With Special Needs In Surakarta - Kanthi Suratih; Erindra Budi Cahyanto; Indarwati Indarwati; Annisa Andriyani (Sekolah Tinggi Ilmu Kesehatan (STIKes) Karya Husada Semarang, 2022)
The number of Children with Special Needs (ABK) in Indonesia reaches 4.2 million people aged between 5 to 14 years or school age. Children with special needs who are born in less than optimal mental and physical conditions certainly make parents sad, unprepared and unable to accept them for various reasons. Moreover, the reason for embarrassing the child as a result is not a few who then treat the child less well and ignore efforts to make the child more independent. Independence will create a positive impact on children's development, so efforts to educate independence are taught to children as early as possible which is synchronized with the child's abilities. The independence of ABK is taught by parents and families who play a role in nurturing, guiding and helping direct children so that they can become independent individuals. Objective: To determine the correlation of parental gait to the level of independence of ABK Surakarta City. This research is a quantitative study, with a cross sectional approach, 60 respondents using the total population method. This research instrument means a questionnaire, the analysis uses the chi square statistical test. The results of the study: bivariate test of parental gait with a level of independence using a chi square p value of 0.006. Conclusion: there is a significant relationship between the role of parents and independence in children with special needs in Surakarta City. Keywords: children with special needs; independence; parents' gaitORANG TUA BERKIPRAH DALAM MENGOPTIMALKAN KEMANDIRIAN ANAK BERKEBUTUHAN KHUSUS DI SURAKARTAABSTRAK Jumlah Anak Berkebutuhan Khusus (ABK) di Indonesia mencapai angka 4,2 juta jiwa yang berusia antara 5 sampai 14 tahun atau usia sekolah. Anak berkebutuhan khusus yang lahir dalam keadaan mental dan fisik yang kurang optimum tentunya membuat orang tua sedih, tidak siap serta tidak mampu menerimanya berbagai alasan. Terlebih lagi alasan membuat malu sebagai akibatnya tidak sedikit yang kemudian memperlakukan anak tadi secara kurang baik dan mengabaikan usaha-usaha untuk membuat anak menjadi lebih mandiri. Kemandirian akan menciptakan dampak yang positif bagi perkembangan anak, maka usaha mendidik kemandirian diajarkan pada anak sedini mungkin yang disinkronkan dengan kemampuan anak. Kemandirian ABK diajarkan oleh orangtua dan keluarga yang berperan dalam mengasuh, membimbing serta membantu mengarahkan anak supaya dapat menjadi pribadi yang mandiri.Tujuan: mengetahui korelasi kiprah orangtua terhadap tingkat kemandirian para ABK Kota Surakarta. Penelitian ini adalah penelitian kuantitatif, dengan pendekatan cross sectional, responden penelitian sebesar 60 responden memakai metode total populasi. Instrumen penelitian ini artinya kuesioner, analisis menggunakan uji statistik chi square. Hasil penelitian: uji bivariate kiprah orangtua dengan tingkat kemandirian menggunakan chi square p value 0,006. kesimpulan: ada hubungan yang significant antara peran orangtua dengan kemandirian pada anak berkebutuhan khusus di Kota Surakarta . Kata kunci : anak berkebutuhan khusus , kemandirian, , kiprah orang tua